(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper presents a demonstration experimental test bench for investigating the dynamic characteristics of an electropneumatic positioning system with High Speed Pneumatic Valves (HSPV) and Pulse Width Modulation (PWM) control. A specialized virtual instrument has been developed for real-time control, data acquisition, and processing. The transient response of the electropneumatic positioning system is examined under various single-step input signals with frequencies ranging from 30 Hz to 70 Hz and varying duty cycles from 30% to 90%. The results are presented graphically, demonstrating that the system exhibits better linear characteristics compared to conventional pneumatic actuation systems.